Kemampuan Metaphorical Thinking dalam Menyelesaikan Soal HOTS SPLDV ditinjau Tipe Gaya Belajar - Kowi, Mohamad Saiful; Fakhriyana, Dina (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
This research aims to analyze students' metaphorical thinking abilities in solving HOTS questions on SPLDV material in terms of auditory, visual, and kinesthetic learning styles. This type of research is descriptive with a qualitative approach. The results of the research show that: 1) the metaphorical thinking abilities of auditory-type students are capable and good at the connect, relate, and explore stages. The transform and analyze stages were quite good. This can be seen from the condition of students who still experience doubts in explaining and make mistakes in solving problems. Students are not yet able to perform well at the experience stage; 2) the metaphorical thinking ability of visual-type students is capable and good at the relate and explore stages. The connect, analyze, and transform stages were quite good. This can be seen from the condition of students who still have not written down complete information and make mistakes in solving problems. Students are not yet able to perform well at the experience stage; 3) the metaphorical thinking ability of kinesthetic type students is capable and good at the relate and transform stages. The connect, explore, and analyze stages were quite good. This can be seen from the condition of students who still experience doubts in explaining and make mistakes in solving problems. Kinesthetic-type students can do quite well at the experience stage.